المقاصد الشرعية الخاصة بالولاية في الزواج ودورها في التصدي لمحاولات تغريب المرأة والأسرة المسلمة (مجلة الواحات للبحوث والدراسات, 2021)
ملخص - اعتبارا لما جاء به التعديل الأخير لقانون الأسرة الذي ينص في المادة 09 مكرر من القانون المعدل الصادر بموجب الأمر 05-02 المؤرخ في 27 فبراير  لعام  2005  على أن للمرأة الحق في مباشرة عقد زواجها، وجعل حضور الولي حضورا شكليا ... فتح المشرع الجزائري بذلك ثغرة قانونية، تلك الثغرة التي قد تفتح بابا لنتائج سيئة قد تعكس سلبيا على المرأة نفسها و على أسرتها و على المجتمع[i] . و بناء على التحديات التي تواجه المرأة والأسرة المسلمة اليوم ، وبناء على الجدل المثار حوله اليوم. جاءت هذه الدراسة لتعالج مشكلة الولي في الزواج من خلال الاحتكام إلى المقاصد الشرعية.الكلمات الدالة: الولاية في الزواج, المقاصد الأصلية, حماية من التغريب    Abstract:  The Subject Of  Wilaya (Tutelage - Guardianship) In Marriage Arouses Much Debate Between Supporters For The Need For Wali's (Tutor) Presence In The Marriage Contract, And Others For Doing It Without Him As They Consider It An Obstacle Before The Woman. This Last Point Of View Is Adopted By Feminist Associations And Movements Aimed At What They Call The Need For Equality Between Women And Men In Accordance With International Human Rights Charters Considering The Woman A Person Of Full Capacity That Does Not Need A Wali Limiting Her Full Freedom Of Choice. The Last Amendment Of The Family Code, By The Order 05-02 Of February 27th, 2005, Stipulates In Article 09 Bis That A Woman Has The Right To Directly Celebrate Her Marriage And That The Presence Of Wali Remains Formal. As A Result, The Algerian Legislator Has Made A Legal Loophole That Can Create Bad And Negative Results On The Woman Herself, Her Family And The Whole Society .Preserving Women, Family And Society Is The Reason Why I Have Underlined The Lines Of This Research In Which I Aim To Emphasize Both Legitimate Objectives (Original And Dependent) Of The Requirement Of Wali. My Objective Is To Correct Some Erroneous Ideas About This Element In Order To Avoid The Growth Of Divorce, And Other Confusions Related To It.Key Words:Wilaya In Marriage, Legitimate Objectives, Expatriating - Emigration